Perkembangan Dana pensiun syariah - Laila Laila kholisa; Lizianil Azizah; Aulia Nailis Salamah; Marfita Hikmatul Aini; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
A pension fund is a collection of assets managed and operated by an institution to produce a pension benefit, namely a periodic payment that is paid to participants at the time and in the manner specified in the provisions that form the basis for administering the pension program where the payment of the benefit is linked to the attainment of age. certain. Meanwhile, sharia pension funds are pension funds that organize pension programs based on Sharia Principles (DSN MUI Fatwa Number: 88/DSN-MUI/XI/2013). The function of pension funds is as insurance, savings and retirement. The main purpose of pension funds is to provide savings for future retirement. One relevant company profile is DPLK Bank Muamalat. This research aims to find out more about Sharia Pension Funds. This research uses a qualitative approach by utilizing in-depth analysis of secondary data from various related literature sources, to understand the perspectives and concepts underlying sharia insurance. The data collection technique in this research uses literature study techniques to obtain a theoretical basis in the form of opinions or writings of legal experts, ulama and other authorized parties, regarding sharia insurance guidelines in Indonesia. This research is descriptive analytical in nature to describe or analyze research results but is not used to make broader conclusions.